The Implementation of a Module “Sahabatku Indonesia” in Favorite Song Units on the Speaking Skills of BIPA Students - Syahraini Nursyifa Camila; Khaerunnisa Khaerunnisa (IAIN Bengkulu, 2023)
Indonesian for Foreign Speakers (BIPA) is an Indonesian language teaching program whose teaching subjects are foreign speakers. The BIPA learning process certainly requires an appropriate and interesting curriculum, teaching materials, and learning methods for the success of foreign speakers in achieving learning goals. The research objective was to find out and describe the effect of the Indonesian best friend module in favorite song units on speaking skills at BIPA level 7. The research method used by researchers is descriptive qualitative. Researchers will describe a data analysis with the method used is descriptive. The data collection technique used is the form of collecting data by observing students. The results of observations on the material in the Indonesian best friend module activities are designed according to level, one of which is the advanced level for students who can already speak Indonesian, namely using the best friend Indonesia BIPA level 7 module which includes the favorite song units. In this study, the researcher refers to SKL (Graduation Competency Standards) at BIPA Level 7 through a Module that focuses on aspects of speaking skills in BIPA learners. The results of this research make students interested in the learning provided by the teacher in using the best friend module Indonesia BIPA level 7 favorite song unit and students prefer speaking skills because learning through speaking skills makes students more active, it is very fun to sing together the same as the title of the song